O pathwork na experiência pessoal pelo olhar da complexidade: uma visão integral de ser humano - Queiroz, Mariela Ballardin Oliveira de (2011)
Although the Cartesian paradigm has led humankind to undisputable scientific and technological developments and valued the intellectual development, this has been achieved at the expense of the emotional and spiritual development of human beings. The crisis has been installed, and either personal or collective longings are no longer met through only one side of that duality, hence the attempt to integrate other aspects in inter and intrapersonal relationships. Such a search may be carried out through approaches that lead to an increased self-awareness, in a selfknowledge process that is involved by an integral view of human being, by attributing equal importance to physical, mental, emotional and spiritual aspects. The challenge is to deal with the complexity stemming from this view, both inside and outside the human being, with the unknown and uncertain in this unfolding of interconnections established between the parts and the whole, in a continuous movement in which disorder is fundamental for a new order to provide new arrangements. All that is meant to find a meaning in life, to improve relationships and build a society coherent with its own ecological nature. Pathwork, as an approach that allows for a selfknowledge work grounded on premises such as the mentioned integration of the aspects of the human being, has been developed from a spiritual conception that understands spirituality as something lived in the experience of self-knowledge learning. From this perspective, this dissertation aimed at understanding the relationship between spirituality and personal development from the point of view of subjects participating in Pathwork groups. The specific objectives were to identify the reasons why the participants sought Pathwork groups; to know the notion of spirituality the participants of Pathwork groups have; to analyze the effects of Pathwork groups on the participants‟ lives. This is a qualitative study, grounded on assumptions of Morin‟s complex systemic thinking, in which the method/path is built along the trajectory, and the observer/researcher is a living, influential part of that way. The study was carried out with participants of Pathwork groups from two regions in Brazil: Rio Grande do Sul/Santa Catarina; and Goias/Tocantins. The coordinator of Pathwork RS/SC was a reference-participant. In order to produce information, we used open interviews, which were recorded and transcribed under the participants‟ consent. Among the results, we have understood the conception of Integral Spirituality as a vehicle to self-knowledge in the sense that, more than integrated, it integrates physical, mental and emotional aspects of human complexity, as well as the social aspect of subject-society-nature-universe complexity. We have found four organizers of the Pathwork system integral spirituality, self-responsibility, contact with negativity, and acceptance which, by means of living learning, relate to one another in a recursive, dialogical, hologrammatic, organizational movement, enabling personal changes regarding physical, mental, emotional and spiritual wellbeing.